2016
DOI: 10.1016/j.foodchem.2016.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Odour characteristics of seafood flavour formulations produced with fish by-products incorporating EPA, DHA and fish oil

Abstract: Abstract.14

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 25 publications
5
37
0
8
Order By: Relevance
“…In particular, 2,4-heptadienal and 2,6-nonadienal, which were found in Con C did not appear in any of the soy milk samples. These two compounds were mainly formed from the lipid oxidation process of n-3 PUFA in the fish oil (Karahadian & Lindsay, 1989;Peinado, Miles, & Koutsidis, 2016). Both the primary and secondary lipid oxidation results clearly showed that lipid oxidation was insignificant for the fish oil enriched soy milk stored at 2 °C.…”
Section: Effect Of Rosemary Extract On Secondary Lipid Oxidation In Fmentioning
confidence: 95%
“…In particular, 2,4-heptadienal and 2,6-nonadienal, which were found in Con C did not appear in any of the soy milk samples. These two compounds were mainly formed from the lipid oxidation process of n-3 PUFA in the fish oil (Karahadian & Lindsay, 1989;Peinado, Miles, & Koutsidis, 2016). Both the primary and secondary lipid oxidation results clearly showed that lipid oxidation was insignificant for the fish oil enriched soy milk stored at 2 °C.…”
Section: Effect Of Rosemary Extract On Secondary Lipid Oxidation In Fmentioning
confidence: 95%
“…The flavour of aquatic products is considered to be one of the most important attributes affecting purchasing preferences of consumers . Numerous studies have reported that ketones are the main flavour compounds in fish and fish products . There is increasing interest regarding better comprehension of the interactions between food matrix and volatile compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The main food sources of -3-PUFA are fish and fish oil, and particularly fish oil is considered as the most important supplement of -3-PUFA [3]. In fact, -3 fatty acids biosynthetic pathways are slow in human body [4]; therefore, it could be beneficial to human health by consumption of fish oil which is rich in -3 fatty acid [5].…”
Section: Introductionmentioning
confidence: 99%